2010
DOI: 10.1007/s12646-010-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

The Two Faces of Familism: A Cross-Cultural Research in India and Italy

Abstract: In the present research, we developed a familism scale comprised of two dimensions, namely support obligations and traditional norms, in order to examine cross-cultural and gender differences in a group of Indian (n=107) and of Italian students (n=106). We hypothesised and found that support obligations were judged more important than traditional norms in both groups. Moreover, the Indian participants considered both dimensions of familism more important than did their Italian counterparts. Indian women gave g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Goldberg and Smith (2009) examined perceived parental skills of U.S. lesbian, gay, and heterosexual couples who were adopting their first child and found that heterosexual and lesbian women initially perceived themselves as more skilled than men. In traditional Italian society, women (mothers, grandmothers, aunts, and daughters) cared for children without any significant support from their husbands or other men in the family (Mucchi-Faina et al 2010). Thus, two women who choose to raise a child together pose a less strange social situation in comparison with two men who raise children by themselves.…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…Goldberg and Smith (2009) examined perceived parental skills of U.S. lesbian, gay, and heterosexual couples who were adopting their first child and found that heterosexual and lesbian women initially perceived themselves as more skilled than men. In traditional Italian society, women (mothers, grandmothers, aunts, and daughters) cared for children without any significant support from their husbands or other men in the family (Mucchi-Faina et al 2010). Thus, two women who choose to raise a child together pose a less strange social situation in comparison with two men who raise children by themselves.…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…Familism describes a strong individual identification with family (Sabogal, Marín, Otero-Sabogal, VanOss Marín, & Perez-Stable, 1987), an emphasis on ideal family relationships as close, and the prioritization of family over all (e.g., Abdou et al, 2010;Campos et al, 2008;Lugo Steidel & Contreras, 2003). Familism is a highly complex construct that has been defined and interpreted in many different ways, but generally reflects attention to the interests of the family and expectations of family cohesion, respect, and obligations; thus, family goals are more important than those of its individual members (Mucchi-Faina, Pacilli & Verma, 2010;Stein et al, 2014). Donati (1985) distinguished between the traditional familistic culture typical of southern Italy (also, see Banfield, 1967) and more contemporary thoughts about family that characterize areas in the north.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are substantial cultural differences in the degree of (un)conditionality and reciprocity of the loyalty that is expected within certain key groups such as the family (e.g., [ 25 27 ]). In some cultures, groups such as the family provide limited care, love and support (for example because care is institutionalized, because love is provided in friendship networks or because support is provided by the welfare state).…”
Section: Introductionmentioning
confidence: 99%